2011
DOI: 10.1097/rlu.0b013e31821c99cd
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Extranodal Lymphoma With PET/CT

Abstract: Hodgkin disease (HD) and non-Hodgkin lymphoma (NHL) represent a spectrum of malignant neoplasms arising from the lymphoid system with an incidence of around 8% of all malignancies. Although they are generally known as tumors of lymph nodes, 25% to 40% of HD/NHL tumors, especially NHL, arise at extranodal sites along the gastrointestinal tract, head and neck, orbit, central and peripheral nervous system, thorax, bone, skin, breast, testis, thyroid, and genitourinary tract. Extranodal involvement is an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“…F-FDG distribution must be confirmed by anatomical imaging modalities, endoscopic studies and biopsies for a definitive diagnosis. Some studies have also reported that structural CT abnormalities and uptake intensities can improve the reliability of 18 F-FDG PET-CT for the differentiation of lymphomatous infiltration from physiological tracer activity, but the uptake pattern has not been found to be a reliable marker (3,4,8,(19)(20)(21)(22). The Waldeyer's ring and lungs are also sites that have relatively high false positive results due to infectious or inflammatory reasons (23).…”
Section: Discussionmentioning
confidence: 99%
“…F-FDG distribution must be confirmed by anatomical imaging modalities, endoscopic studies and biopsies for a definitive diagnosis. Some studies have also reported that structural CT abnormalities and uptake intensities can improve the reliability of 18 F-FDG PET-CT for the differentiation of lymphomatous infiltration from physiological tracer activity, but the uptake pattern has not been found to be a reliable marker (3,4,8,(19)(20)(21)(22). The Waldeyer's ring and lungs are also sites that have relatively high false positive results due to infectious or inflammatory reasons (23).…”
Section: Discussionmentioning
confidence: 99%
“…PET/CT can detect multifocal renal involvement or involvement of adjacent abdominal lymph nodes. Detection of metabolically active lymph nodes increases diagnostic certainty since interpretation of renal lymphoma can be hampered by physiologic renal uptake of FDG ( 94 ). Diffuse renal lymphoma results in diffusely increased FDG uptake ( 95 ).…”
Section: Renal Cell Cancermentioning
confidence: 99%
“…Hybrid positron emission tomography (PET)/computed tomography (CT) integrates 18 F-fluorodeoxyglucose (FDG) PET and CT scanning, thus simultaneously providing functional, metabolic information based on PET and structural, anatomical information based on CT[8-10]. A growing number of studies have supported the application of 18 F-FDG PET/CT in initial staging, treatment response assessment, and follow-up of patients with gastric lymphoma of various histological subtypes[11-14].…”
Section: Introductionmentioning
confidence: 99%